A Phytoconstituents and Pharmacological Activities Guided Review on Nelumbo nucifera Gaertn - Patel, Arvind Kumar; Chandra, Phool; Sachan, Neetu; Singh, Neha (Current Traditional Medicine, 2025)
BackgroundHerbal drugs are essential as well as valuable gifts of nature. Plants have been known as a conventional wellspring of medications since they contain metabolites of the high synthetic variety of phytochemicals.ObjectiveThis review is intended to provide a detailed description related to the phytoconstituents and pharmacological activities of Nelumbo nucifera Gaertn.MethodsThe study was performed by a literature survey of original research articles published in Pubmed, ScienceDirect, Web of Science, Scopus, and Google, using keywords such as “Nelumbo nucifera”, “phytoconstituent” and “pharmacological activity.”ResultsIn traditional medicine, N. nucifera was used as an emollient, diuretic, and astringent, and it was used to treat diarrhea, homeostasis, and tissue inflammation. Its rhizome was utilized in treating diabetes and as an anti-inflammatory because it contains steroidal terpenoids. At the same time, its leaves were used as an effective treatment for hemoptysis, hematuria, hematemesis, and epistaxis. In conventional medicine, seeds treat skin infections, cancerous growth, tissue inflammation, and toxins. On behalf of various research on a different part of N. nucifera have shown many pharmacological actions like anticancer, antioxidant, anti-ischemic, antiviral, antiobesity, hypocholesterolemic, lipolytic, antipyretic, hypoglycaemic, hepatoprotective, antidiarrhoeal, antibacterial, antifungal, anti-inflammatory, and diuretic activities. Different parts of lotus have been used as healthy foods. Therefore, it is also viewed as a potential nutraceutical source.ConclusionIn this study, we conclude that many phytoconstituents are present in N. nucifera that are responsible for producing various types of pharmacological activities.
Keywords: traditional uses